Clinical characteristics and outcomes of childhood-onset ANCA-associated vasculitis: a French nationwide study - Sacri, A.-S.; Chambaraud, T.; Ranchin, B.; Florkin, B.; See, H.; Decramer, S.; Flodrops, H.; Ulinski, T.; Allain-Launay, E.; Boyer, O.; Dunand, O.; Fischbach, M.; et al. (Nephrology, dialysis, transplantation, 2015)
Data on anti-neutrophil cytoplasmic antibody (ANCA)-associated vasculitis are scarce in children. The current study is aimed at describing the clinical features and outcomes of childhood-onset ANCA-associated vasculitis (AAV). We conducted a retrospective French multicentre study involving patients in whom AAV was diagnosed before the age of 18 years. Inclusion criteria were (i) granulomatosis with polyangiitis (GPA) or microscopic polyangiitis (MPA) according to classification criteria of the European League Against Rheumatism/Paediatric Rheumatology European Society, and (ii) ANCA positivity. Patient and renal survival were analysed. Among 66 children included, 80% were female, 42% had GPA and 58% MPA including renal-limited vasculitis, 67% were pANCA+ and 33% cANCA+. The mean incidence of reported cases increased to 0.45 per million children/year in the period 2006-10. Median age at diagnosis was 11.5 years, and median time to diagnosis was 1 month. Initial symptoms included fever and fatigue (79%), skin lesions (41%), arthritis (42%), pulmonary (45%) and renal involvement (88%). Clinical features were similar between GPA and MPA with the exception of upper airway impairment (28%) specific of GPA. Ninety percent of the patients achieved remission after induction treatment. After a median follow-up of 5.2 years, 4 patients (6%) died, corresponding to a mortality rate of 1.2 per 100 person-years, and 22 patients (34%) developed end-stage renal disease (ESRD). Renal survival was 74, 70 and 59% at 1, 5 and 10 years, respectively. In a multivariable Cox regression model, baseline glomerular filtration rate, ethnic origin, histopathological classification and era of treatment were associated with the occurrence of ESRD. Relapse-free survival was 57% at 5 years and 34% at 10 years of follow-up. Patient and renal outcome did not significantly differ between GPA and MPA. Childhood-onset AAV is a rare disease characterized by female predominance, delayed diagnosis, frequent renal impairment and a high remission rate. Baseline GFR and new histopathological classification system are strong predictors of ESRD. Renal survival in childhood AAV has improved over time.